Spinning Hopf solitons on S-3 x R - do Bonfim, ACR; Ferreira, L. A. (Int School Advanced Studies, 2006)
We consider a field theory with target space being the two dimensional sphere S-2 and defined on the space-time S-3 x R. The Lagrangean is the square of the pull-back of the area form on S-2. It is invariant under the conformal group SO(4, 2) and the infinite dimensional group of area preserving diffeomorphisms of S-2. We construct an infinite number of exact soliton solutions with non-trivial Hopf topological charges. The solutions spin with a frequency which is bounded above by a quantity proportional to the inverse of the radius of S-3. The construction of the solutions is made possible by an ansatz which explores the conformal symmetry and a U(1) subgroup of the area preserving diffeomorphism group.
Keywords: integrable field theories; integrable hierarchies; sigma models